Peacekeeping and the Gender Regime: Dutch Female Peacekeepers in Bosnia and Kosovo - Sion, Liora (Journal of contemporary ethnography, 2008)
This article addresses the issue of women participation in peacekeeping missions by focusing on two North Atlantic Treaty Organization Dutch peacekeeping units in Bosnia (SFOR8) and Kosovo (KFOR2). I argue that soldiers are ambivalent toward what is perceived the “feminine” aspects of peace missions. Although peacekeeping is a new military model, it reproduces the same traditional combat-oriented mind-set of gender roles. Therefore Dutch female soldiers are limited in their ability to perform and contribute to peace missions. Both peacekeeping missions and female soldiers are confusing for the soldiers, especially for the more hypermasculine Bulldog infantry soldiers. Both represent a blurred new reality in which the comfort of the all-male unit and black-and-white combat situations are replaced by women in what were traditionally men's roles and the fuzzy environment of peacekeeping. At the same time, both are also necessary: peacekeeping, although not desirable, has become the main function for Dutch soldiers, and women are still a small minority, although they gain importance in the army. Present government policy prescribes a gender mainstreaming approach to recruiting, partly due to a lack of qualified male personnel, especially after the end of the draft in 1996.